Pengaruh Corporate Social Responsibility (CSR) Terhadap Reputasi Dan Kinerja Keuangan Bank Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2021-2023 - Astuti, Ayi; Nuraliaty, Ayke; Utami, Indri (Gorontalo Management Research, 2025)
This study explores the impact of Corporate Social Responsibility (CSR) on corporate reputation and financial performance in the banking industry. With increasing public attention to ethical and sustainable business practices, this study aims to identify the relationship between CSR implementation, public image, and bank financial results as measured by Return on Asset (ROA). The methodology used is a quantitative approach with regression analysis of data obtained from the annual reports of banks listed on the Indonesia Stock Exchange and the CSR index. The results show that banks that actively implement CSR tend to have a better reputation in the eyes of the public and stakeholders, as well as show an increase in long-term financial performance as measured by revenue and net profit growth. In addition, the analysis shows that CSR contributes positively to ROA with a significant correlation coefficient. These findings suggest that CSR not only fulfills social responsibility but is also an important strategy to improve banks' financial performance. This study emphasizes the need for bank management to integrate CSR as part of their long-term strategy.